The place of older people in the 5.0 society – the rightful presence or cyberexclusion - Adamczyk, Monika; Karpiuk, Miroslaw; Soler, Urszula (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In the extremely dynamically developing societies of the 21st century, the problems that older people face due to the rapid development of technology are discussed increasingly often. The pace of technological change that is not adapted to their capabilities also causes rapid changes in society and causes many problems for older people. Are we not falling into "demographic panics" and "demographic determinism"? Could population projections derail all positive options for human development in a modern 5.0 society model? Or, just the opposite, can the demographic ageing of the population be a trigger for creativity and innovative approaches in the provision of goods and services in the area of new technologies? To what extent are we prepared, also digitally, for the process of advanced population ageing? Will the new social model, which is Society 5.0, be a model in which older people can fully participate, or will they be excluded in many aspects? What effects will this new technological and social revolution have on older people? These questions, among others, will be answered in this article. In this text, we will look beyond an individual for the social implications of population ageing by analysing the processes and phenomena affecting whole societies and the institutions they create at the macro-social level.